Recent Progress in Some Aircraft Technologies - Agarwal, Ramesh K. (IntechOpen, 2016)
The book describes the recent progress in some engine technologies and active flow control and morphing technologies and in topics related to aeroacoustics and aircraft controllers. Both the researchers and students should find the material useful in their work.